Wildland Weeds: Arrowhead Vine, Syngonium podophyllum - Eric C. Morgan; William A. Overholt; Kenneth A. Langeland (EDIS)
For years, people have come to south Florida to escape the cold weather and enjoy the subtropical climate. With this migration, horticulturists and amateur plant enthusiasts have introduced many species of exotic plants from the tropics, attempting to create their own tropical oases. While most of these plants either quickly perish or never spread outside of the backyard, a few escape and spread to adjoining natural and semi-disturbed areas and create persistent self-perpetuating populations. These plants are called invasive, and they can wreak havoc in the environments of their adopted home. Arrowhead vine (Syngonium podophyllum) is one of these destructive invaders. This document is ENY-715, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2004.